Identifying and priority setting indicators of integration and integrable units in hospitals of Tabriz University of Medical Sciences from the perspective of health experts - yalda mousazadeh; hossein jabari beirami; ali janati; mohammad asghari jafarabadi; ali ebadi (Journal of Analytical Research in Clinical Medicine, 2013)
BACKGROUND: Hospitals face major challenges such as lack of resources, increase in costs, and particularly severelimitations by sanctions that lead to integration in hospitals. This study was conducted to identify and prioritize theindicators of integration and integrable hospital units based on the experts' perspective. METHODS: The present study was a three phase qualitative, applied survey. The first phase included a review of thefundamental concepts. The second phase included three focus group discussions with presence of experts to identifynecessary indicators for the implementation of integration strategy and the hospital units that can be integrated based onindicators. In the third phase, Delphi's questionnaire was prepared based on Likert's scale for prioritizing and choosingthe indicators and hospital units. RESULTS: 9 indicators and 29 hospital units were identified during focus group discussions. Consensus was achievedon 9 indicators and 23 units out of 29 units based on the three stages of Delphi's questionnaire. The most importantindicators were cost and parallelism in tasks (consensus = 95.2%). Service availability and responsibility(consensus = 71.4%) were the least important indicators. The supporting units had the greatest potential (45.45% oftotal units) of merging. Emergency, inpatient wards, management, and chairmanship units were not candidates forintegration according to the viewpoint of experts. CONCLUSIONS: Integration will lead to efficiency in resources management, avoids parallelism in tasks, increasesservice availability, and reduces costs. Integration capability exists in many parts of the hospital; therefore, it can beused in the hospitals. Furthermore, it is necessary to define clear indicators for measuring the success of this strategy.